Current concepts in the diagnosis of pancreatitis in dags and cats - XENOULIS (Π.Γ. ΞΕΝΟΥΛΗΣ), P. G.; STEINER, J. M. (Journal of the Hellenic Veterinary Medical Society, 2017)
Pancreatitis is the most common disorder of the exocrine pancreas in both dogs and cats. Ante-mortem diagnosis of pancreatitis can be challenging and the majority of cases is believed to remain undiagnosed. Complete blood count, serum biochemistry profile and urinalysis should always be performed in dogs and cats suspected of having pancreatitis, although findings are non-specific for pancreatitis. Abdominal ultrasonography is very useful for the diagnosis of pancreatitis, although the diagnostic utility depends largely on the clinician's experience. Abdominal radiography is a useful diagnostic tool for the exclusion of other diseases that may cause similar clinical signs to those of pancreatitis. Computed tomography has not been shown to be useful for the diagnosis of canine or feline pancreatitis and thus it cannot be recommended. Histopathologic examination of the pancreas is the only method to definitively diagnose pancreatitis, but exclusion of the disease is difficult. Serum amylase and lipase activities are of no clinical value in cats and should not be used for the diagnosis of pancreatitis in this species. In dogs, these tests may still have some clinical utility as an initial approach to animals with suspected pancreatitis. Due to its low sensitivity, serum TLI concentrations are considered of limited usefulness in diagnosing pancreatitis in dogs and cats. Finally, serum PLI concentrations are currently considered to be the most sensitive and specific test for the diagnosis of canine and feline pancreatitis.